已知[img=162x61]1802e93dc9d46aa.png[/img],则[img=36x44]1802e93dd254314.png[/img]( )
A: [img=42x45]1802e93dda25a9d.png[/img]
B: [img=58x45]1802e93de24f4ea.png[/img]
C: [img=42x45]1802e93deb62a62.png[/img]
D: [img=58x45]1802e93df2ece05.png[/img]
A: [img=42x45]1802e93dda25a9d.png[/img]
B: [img=58x45]1802e93de24f4ea.png[/img]
C: [img=42x45]1802e93deb62a62.png[/img]
D: [img=58x45]1802e93df2ece05.png[/img]
举一反三
- 已知[img=162x61]1802e96d24f38ef.png[/img],则[img=36x44]1802e96d2c994e6.png[/img]( ) A: [img=42x45]1802e96d34ab2aa.png[/img] B: [img=58x45]1802e96d3cef0bb.png[/img] C: [img=42x45]1802e96d455b231.png[/img] D: [img=58x45]1802e96d4dee4a1.png[/img]
- 已知[img=162x61]1802e98003298d4.png[/img],则[img=36x44]1802e9800b1ebfd.png[/img]( ) A: [img=42x45]1802e980124db0d.png[/img] B: [img=58x45]1802e9801a76362.png[/img] C: [img=42x45]1802e98022302f3.png[/img] D: [img=58x45]1802e980295a4b2.png[/img]
- 设随机变量X~P([img=11x19]17de5dcc6b8a740.png[/img]),且已知E [(X-1)(X-2)]=1,则[img=11x19]17de5dcc6b8a740.png[/img]= .
- 设随机变量X~P([img=11x19]180317950bd340c.png[/img]),且已知E [(X-1)(X-2)]=1,则[img=11x19]180317950bd340c.png[/img]= .
- 函数[img=103x33]17e0b09051e076c.jpg[/img]的反函数是 未知类型:{'options': ['y=1-3cosx,x[img=6x11]17e0b0905fe87f4.jpg[/img][0,[img=8x11]17e0a7285a871a0.jpg[/img]]', ' y=1+3cosx,x[img=6x11]17e0b0905fe87f4.jpg[/img][0,[img=8x11]17e0a7285a871a0.jpg[/img]]', ' y=1-3sinx,x[img=6x11]17e0b0905fe87f4.jpg[/img][0,[img=8x11]17e0a7285a871a0.jpg[/img]]', ' y=1+3sinx,x[img=6x11]17e0b0905fe87f4.jpg[/img][0,[img=8x11]17e0a7285a871a0.jpg[/img]]'], 'type': 102}